Long-term Care in the Agenda: The Case of Chile. Issue 1 (31st December 2023) - Villalobos Dintrans, Pablo; Alliende, Trinidad; Palacios, Josefa; Contrucci, Isabel; Browne, Jorge
ABSTRACT: The Chilean presidential elections of 2021 included an unprecedented topic in the country's political debate: long-term care (LTC). Although some public policies and programs have been in place for at least 20 years, during this 2021 presidential election LTC was mentioned for the first time in a political campaign. Five out of seven candidates highlighted the importance of LTC in their proposals and designed policies to address it. Why did this topic gain momentum as a campaign topic in 2021? What can explain the sudden inclusion of a new topic on the Chilean political agenda? Using Kingdon's multiple streams framework this article aims to understand the factors explaining the inclusion of LTC in the Chilean political agenda during the past presidential elections. A two-step qualitative research design was performed using a case study approach. As a first step, a documentary analysis of the campaign programs was conducted searching for references to LTC proposals. In a second step, semi-structured interviews were carried out with representatives from three of the seven campaign teams, including the teams that reached the ballotage. Data were analyzed using Kingdon's multiple streams framework. Results showed that the availability of national data on LTC needs helped highlight the problem and acted as a facilitator for advocacy; international organizations and other countries' experiences in implementing LTC systems served as policy entrepreneurs; and four events—the feminist movement, the social outbreak with the constitutional process, and the COVID-19 pandemic—pushed LTC forward on the political agenda. The case of Chile illustrates how Kingdon's framework can be used to identify facilitators for LTC inclusion on the political agenda, serving as an example for other countries facing similar issues and fostering the global debate around the increase in LTC needs.